The Effect of Tiktok Live Streaming Shopping and Perceived Enjoyment Toward Online Impulsive Buying Behavior with The Moderating Variable of Trust - Herlina, Leni (International Journal of Business Studies, 2023)
This research studied the effect of social-media influencers, product price, and purchase convenience toward perceived enjoyment to online impulsive buying behavior with the moderating variable of trust on Tiktok live shopping consumers in Indonesia. This research used a quantitative design by developing an online questionnaire to collect data through purposive sampling with the criteria: 1). Age of 17 - 58 years old, 2). Reside in the Jabodetabek area, 3). Use Tiktok in their daily life, 4) Happened to join Tiktok live streaming shopping, and 5). Buy the product during that live streaming. The data was collected on February 2023 and the number of respondents was 105. SPSS 29.0 was used for data preparation and SmartPLS 4.0 was used to analyze the data and the hypothesis accordingly. The result showed that there was a significantly positive effect of social-media influencers, product price, and purchase convenience on perceived enjoyment. In addition, perceived enjoyment also has a positive effect on online impulsive buying behavior. However, trust did not play a moderating role to the effect of perceived enjoyment to online impulsive buying behavior. The findings suggest that stores Tiktok live shopping should collaborate with an influencer who is knowledgeable, understand the product well, and is communicative. Hence, they can create a lively and persuasive shopping experience. On the other hand, the online seller can create special prices or discounts during the special season such as payday, national big day, religious celebration day, or national shopping day.